Royal road from geometric to discrete optics - Wolf, Kurt Bernardo (Photonics Letters of Poland, 2015)
We present an optical design based on a Ritchey-Chretien Telescope to carry out solar observations at THz frequencies (mid-infrared wavelengths), looking for both, good spatial coverage and resolution. Our goal is to have a field of view that covers the full solar disk, but at the same time to take advantage of the reduction of aberrations in this kind of telescopes so that we can be close the dispersion limit when making solar images. The design is going to be applied in a 120x160 array but it is done so that it allows the scaling to other arrays that could be further implemented. Here we describe the conceptual design and some of the first tests to components for the camera showing the feasibility of building of a good instrument for solar observation based on commercial components. Full Text: PDF References P. Kaufmann, Jean-Pierre Raulin, C. G. Giménez de Castro, Hugo Levato, Dale E. Gary, Joaquim E. R. Costa, Adolfo Marun, Pablo Pereyra, Adriana V. R. Silva and Emilia Correia, "A New Solar Burst Spectral Component Emitting Only in the Terahertz Range", The APJ., 603 : L121?L124 (2004). CrossRef P. J. Turon and P. J. Léna, "High resolution solar images at 10 microns: Sunspot details and photometry", Solar Physics, vol 14, 112-114 (1970). CrossRef Kaufmann, P., Correia, E., Costa, J. E. R., & Zodi Vaz, A. M., "A synchrotron/inverse Compton interpretation of a solar burst producing fast pulses at lambda less than 3-mm and hard X-rays", A&A, 157, 11 (1986) DirectLink A. M. Melo, P. Kaufmann, A. S. Kudaka, and J.-P. Raulin, "A New Setup for Ground-based Measurements of Solar Activity at 10 ?m", Astr. Soc. Pacific, 118: 1558?1563 (2006). CrossRef P. Kaufmann, S. M. White, S. L. Freeland, R. Marcon, L. O. T. Fernandes, A. S. Kudaka, R. V. de Souza, J. L. Aballay, G. Fernandez, R. Godoy, A. Marun, A. Valio, J.-P. Raulin, and C. G. Giménez de Castro, "A Bright Impulsive Solar Burst Detected at 30 THz", The APJ., 768:134 (2013). CrossRef Matthew J. Penn,"Infrared Solar Physics", Rev. Solar Phys., 11 (2014). CrossRef Gordon J. Stacey, "New Ground Based Facilities for THz Astronomy", 19th International Symposium on Space Terahertz Technology (2008). DirectLink Christopher E. Groppi and Jonathan H. Kawamura, "Coherent Detector Arrays for Terahertz Astrophysics Applications", IEEE Transactions on Therahertz Science and Technology, Vol. 1, 1 (2011). CrossRef Pierre Kaufmann, Rogério Marcon, André Abrantes, Emilio C. Bortolucci, Luis Olavo T, Fernandez, Grigory I. Kripotov, et al., "THz photometers for solar flare observations from space", Springer Exerimental Astronomy, Vol. 37 (2014). CrossRef Peter H. Siegel, "Editorial: The transactions goes monthly", IEEE Transactions on Microwave Theory and Techniques, Vol. 50, 3 (2002). CrossRef M. Moreno, A. Kosarev, A. Torres, R. Ambrosio, "Fabrication and performance comparison of planar and sandwich structures of micro-bolometers with Ge thermo-sensing layer", ScienceDirect (2007). DirectLink Mario Moreno, Andrey Kosarev, Alfonso Torres, Roberto Ambrosio, "MICROBOLOMETERS FABRICATED WITH SURFACE MICROMACHINING WITH a-Si-Ge: H THERMO-SENSING FILMS" Int. Journal of High speed Electronics and System, Vol. 18, No. 4 (2008). CrossRef Ricardo Jiménez Zavala, M. Sc. Thesys INAOE (2013). Juan Carlos García Santos, Berenice Rodríguez Pedroza, Juan Salvador Palacios Fonseca, José Eduardo Mendoza Torres, Somi XXIX (2014). Berenice Rodríguez Pedroza, Juan Carlos García Santos, José Eduardo Mendoza Torres, Miguel Octavio Arias Estrada, SOMI XXIX (2014). M.C. Juan Salvador Palacios Fonseca, Dr. Jose Eduardo Mendoza Torres, Dr. Miguel Velázquez de la Rosa, SOMI XXIX (2014).